(untitled) (XXI Century. Spanish Literature and Culture, 2004)
Luis García Montero, revitalizes Spanish poetry through a new poetic generation of a realist and figurative disposition that establish an identified subject between poet and city, a poetic voice which is clearly urban, closely linked with the world of affection. Additionally, we find the two sides of the same poetic exercise: private morality against public ethics; a fight which entails a progressive utopia towards postmodernist realism.